Analisis Komparatif Tingkat Transparansi antara Bank Konvensional dan Bank Syariah di Indonesia - Nababan, Ailen Romauli; Teri, Teri; Taliding, Arianto; Tikupadang, Wendy Kala (Tangible Journal, 2025)
This study aims to conduct a comparative analysis of the transparency level between Conventional Banks and Islamic Banks in Indonesia during the period 2019–2023. Transparency is considered an essential factor in building public trust, investor confidence, and regulatory compliance, as well as being a key indicator of good corporate governance in the banking industry. The research employs a qualitative descriptive approach, analyzing official documents such as annual reports and financial statements published through the Indonesia Stock Exchange (IDX). The findings reveal that BRI consistently emphasizes technical aspects of disclosure, including financial reporting, business risk, and regulatory compliance. Meanwhile, BSI demonstrates a significant improvement in transparency, particularly after the merger in 2021, with greater emphasis on ethical dimensions, sharia contracts, profit-sharing mechanisms, and sharia-based governance. These results indicate that the main difference in transparency characteristics lies not only in reporting format but also in the underlying values guiding each banking system’s operations.